POISSON REGRESSION OF DAMAGE PRODUCT SALES USING MCMC - Marliana, Reny Rian; Padmadisastra, Septiadi (Indonesian Journal of Statistics and Applications, 2018)
In this paper a model for the number of â€œdamageâ€ product sales is studied. The product sales are run into underreporting counts, caused by a delay on input process of the system called sales cycle. The goal of the study is to estimate the parameters of the regression model of product sales on an explanatory variable. It is the actual number of product sales. The model used is a mixture of the Poisson and the Binomial distributions. The parameters of the regression model are estimated by a Bayesian approach and Markov Chain Monte Carlo simulation using Gibbs sampling algorithm. The results of estimation clearly showed a gap between undamage product sales and the actual number. The gap is the number of damaged product sales.